2019
DOI: 10.1002/aic.16813
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous effect of particle size and solid concentration on the hydrodynamics of slurry bubble column reactors

Abstract: The simultaneous effect of particle size and concentration on the total gas holdup of slurry bubble column reactors was investigated in this work. The total gas holdup was measured for air-water-glass beads systems. Three solid concentrations and three particle diameters were used. It was found that increasing particle size at high constant concentration decreases gas holdup. Moreover, increasing solid concentration decreases gas holdup and this decreasing effect is higher for larger particles. Also, solid par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 42 publications
2
33
0
Order By: Relevance
“…Regarding the effects of solid size on the gas hold-up, Rabha et al [37], for instance, reported that at low values of solid size and concentration, the particle size cannot affect gas hold-up while at higher values of solid concentration and size, increasing the solid size decreases the gas hold-up. The same results were also reported by Lakhdissi et al [23]. On the other hand, the experiments of Li et al [50] revealed that increasing the solid size cannot affect the gas hold-up even for high concentrations of solid (up to 40 vol %).…”
Section: Flow Regimesupporting
confidence: 85%
See 1 more Smart Citation
“…Regarding the effects of solid size on the gas hold-up, Rabha et al [37], for instance, reported that at low values of solid size and concentration, the particle size cannot affect gas hold-up while at higher values of solid concentration and size, increasing the solid size decreases the gas hold-up. The same results were also reported by Lakhdissi et al [23]. On the other hand, the experiments of Li et al [50] revealed that increasing the solid size cannot affect the gas hold-up even for high concentrations of solid (up to 40 vol %).…”
Section: Flow Regimesupporting
confidence: 85%
“…Lakhdissi et al [23] studied the effects of particle concentration and size on the gas hold-up in an air-water-glass beads systems. Their experiments showed that at a constant solid concentration, increasing the solid size had no influence on the total gas hold-up at low solid concentrations (up to 3 % (v/v)) while increasing the solid size leads to decreasing gas hold-up at the higher solid particle's concentrations (5 % (v/v)).…”
Section: Flow Regimementioning
confidence: 99%
“…Different researchers have reached different conclusions on the effect of superficial gas velocity on bubble size: with the increase of superficial gas velocity, bubble size increases, 10−12 decreases, 13,14 or has no obvious change. 15,16 In addition, solid particles can affect bubble dynamics by changing the viscosity and density of the liquid phase and the collision strength between bubbles and particles: 17 the increase in particle concentration promotes bubble coalescence by increasing the viscosity of the slurry. 18 Ojima et al 19 attributed the enhancement of bubble coalescence when the particle size decreases to an increase in the number density of particles in the liquid film around the bubble, while Lakhdissi et al 17 attributed it to a decrease in bubble−particle collision efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…It was concluded that the bubble size distribution at the inlet of the column did not affect the distribution inside the column. Lakhdissi et al [17] investigated the impact of particle diameter and concentration on gas holdup for a slurry bubble column. The process consisted of three phases (air, water, and glass beads).…”
Section: Introductionmentioning
confidence: 99%
“…However, the holdup was independent at higher concentrations. They also mentioned that, in general, increasing the solids concentration reduces the gas holdup and therefore increases the bubble diameter [17]. Rabha et al [19] examined the effect of particle size (50-150 µm) and solids concentration Cs of (0-0.20) on the hydrodynamics of a slurry bubble column by utilizing ultrafast electron beam X-ray tomography.…”
Section: Introductionmentioning
confidence: 99%